Non-Gaussian behaviour of a self-propelled particle on a substrate - ten Hagen, B.; van Teeffelen, S.; Löwen, H. (Condensed Matter Physics, 2009)
The overdamped Brownian motion of a self-propelled particle which is driven by a projected internal force is studied by solving the Langevin equation analytically. The active particle under study is restricted to move along a linear channel. The direction of its internal force is orientationally diffusing on a unit circle in a plane perpendicular to the substrate. An additional time-dependent torque is acting on the internal force orientation. The model is relevant for active particles like catalytically driven Janus particles and bacteria moving on a substrate. Analytical results for the rst four time-dependent displacement moments are presented and analysed for several special situations. For a vanishing torque, there is a significant dynamical non-Gaussian behaviour at finite times t as signalled by a non-vanishing normalized kurtosis in the particle displacement which approaches zero for long time with a 1/t long-time tail. На основi знаходження аналiтичного розв’язку рiвняння Ланжевена дослiджується згасаючий броунiвський рух самохiдної частинки, що керується вiдпроектованою внутрiшньою силою. Рух такої “активної” частинки обмежується вздовж лiнiйного каналу, а напрямок внутрiшньої сили, що дiє на неї, орiєнтацiйно дифундує на одиничному колi в площинi, перпендикулярнiй до субстрату. Додатковий залежний вiд часу момент сили також впливає на орiєнтацiю внутрiшньої сили. Така модель є актуальною для активних частинок на кшталт каталiтично керованих частинок Януса або ж бактерiй, що рухаються на поверхнi субстрату. Для чотирьох перших моментiв змiщення частинки отримано аналiтичнi результати, якi аналiзуються для кiлькох спецiальних ситуацiй. Для моменту сил, що прямує до нуля, спостерiгається цiкава негаусова динамiчна поведiнка при скiнчених часах t, про що сигналiзує незникаюча величина нормалiзованого коефiцiєнта ексцесу , який спадає як 1/t при великих часах.